Effects of vacuum impregnation and calcium compounds on preservation of the microstructure and quality of frozen Aloe vera (Aloe barbadensis Miller) - Siranut Wangsomboonsiri; Masubon Thongngam; Suvimol Charoensiddhi; Danar Praseptiangga; Achmad Ridwan Ariyantoro; Sarunya Laovitthayanggoon; Panuwat Suppakul; Ulaiwan Withayagiat; Waraporn Boonsupthip (Journal of Agriculture and Food Research)
Various calcium compounds in powder form, rather than solution form, were directly added to Aloe vera chunks and were expected to diffuse effectively with the assistance of vacuum impregnation, providing different degrees of cellular integrity protection against freezing damage. The objective of this study was to investigate how different calcium compounds (calcium chloride (CaCl2), calcium lactate (CaL), and calcium carbonate (CaCO3)) and VI preserve the quality of frozen Aloe vera. Fresh Aloe vera chunks were treated with the calcium compounds in a powder form, optional VI treatment (varying vacuum holding time (t1) and relaxation time (t2)) and then frozen, thawed and drained. Microscopic analyses, including light and fluorescence imaging, revealed that cellular damage was influenced by both VI conditions and the type of calcium compound. Without VI, CaCl2 caused substantial cellular damage and increased liquid loss, while CaL and CaCO3 had less pronounced effects. VI alone caused cell loosening and rupture, but when combined with calcium compounds, it provided significant protection to the cellular structure of freeze-thawed Aloe vera, likely improving textural hardness and reducing liquid loss. Notably, CaCl2 reduced pH, CaCO3 increased pH, and CaCl2 and CaL led to higher total leaked liquid (TLL), although they enhanced tissue hardness when effectively impregnated. The extent of cellular damage and quality improvements varied with t1, t2, and calcium compound type and concentration. Among the tested compounds, CaL was most retained in the Aloe vera matrix (high calcium content and electrical conductivity) and effective in preserving cellular integrity, whereas CaCl2 was least effective. VI offers potential benefits for improving the quality of frozen Aloe vera, emphasizing the need for optimization of calcium concentration and VI conditions to balance cellular protection and quality enhancement. CaL shows great potential for calcium fortification in frozen foods.